2014
DOI: 10.1016/j.neuropharm.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Ventromedial prefrontal cortex regulates depressive-like behavior and rapid eye movement sleep in the rat

Abstract: Major depressive disorder (MDD) is a debilitating disease with symptoms like persistent depressed mood and sleep disturbances. The prefrontal cortex (PFC) has been implicated as an important structure in the neural circuitry of MDD, with pronounced abnormalities in blood flow and metabolic activity in PFC subregions, including the subgenual cingulate cortex (sgACC, or Brodmann area 25). In addition, deep brain stimulation in the sgACC has recently been shown to alleviate treatment-resistant depression. Depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 48 publications
0
35
1
Order By: Relevance
“…Vialou and colleagues demonstrate that CCK likely released by GABAergic interneurons produces low neuronal activity in the vmPFC by social defeat (Vialou et al, 2014). Our recent study (Chang et al , 2014) shows that lesions of the vmPFC but not the dmPFC reduce REM sleep latency and increase REM sleep amounts and immobile time in forced swim test (FST) in rats. These REM sleep changes are in line with human MDD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vialou and colleagues demonstrate that CCK likely released by GABAergic interneurons produces low neuronal activity in the vmPFC by social defeat (Vialou et al, 2014). Our recent study (Chang et al , 2014) shows that lesions of the vmPFC but not the dmPFC reduce REM sleep latency and increase REM sleep amounts and immobile time in forced swim test (FST) in rats. These REM sleep changes are in line with human MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic restraint stress leads to dendritic atrophy in the rat medial PFC (mPFC), including reduced length and total branch numbers of apical dendrites in pyramidal cells (Brown, 2005; Cook and Wellman, 2004; Izquierdo et al , 2006; Radley et al , 2004), while antidepressant treatment increases markers of neuroplasticity (Sairanen et al , 2007) and changes in cell morphology in the PFC (Benes and Vincent, 1991; Li et al , 2010). Our recent study shows that the lesioning the vmPFC reduces REM sleep latency, increases REM sleep amounts, and increases immobile time in forced swim test (FST) in rats (Chang et al , 2014). These changes of REM sleep and hopelessness are consistent in behaviors of unipolar and bipolar depression in human.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced volume in subgenual anterior cingulate cortex (sgACC; a portion of human vmPFC), which includes Brodmann area (BA) 25 posteriorly and parts of BA24 and BA32 anteriorly [3] has been observed in depressed patients [4], and spine loss and decreased dendritic arborization in the vmPFC (including prelimbic and infralimbic cortexes) have been reported in rodents following chronic stress exposure [5]. Recent preclinical studies also revealed that vmPFC stimulation [6] and lesion [7] induce antidepressant and prodepressant effects in rodents, respectively. VGF (non-acronymic) is a neuropeptide precursor that is robustly regulated by neurotrophic growth factors [8], including brain-derived neurotrophic factor (BDNF).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that a limbic-auditory interaction could have constituted a ''noise-cancelling'' system, comprising mainly nodes of the thalamus, nucleus accumbens (NAc) and vMPFC, in which the vMPFC specializes in orienting attentional and emotional modulation into inhibiting the unwanted sensory signals through NAc and thalamus (Rauschecker et al, 2010;Leaver et al, 2011). Furthermore, activities in this region have been found to be related to processing the pleasantness of the stimuli (Sabatinelli et al, 2007;Junghofer et al, 2017), and animal studies have found that lesions to this region could induce depression-like behaviors in rat (Chang et al, 2014). VMPFC abnormalities have also been found in tinnitus patients with both structural (Mühlau et al, 2006;Leaver et al, 2011) and functional evidences (Seydell-Greenwald et al, 2012).…”
Section: Discussionmentioning
confidence: 99%